2023
DOI: 10.6007/ijarbss/v13-i4/16665
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Situational Interest As Motivation To Learn Online

Abstract: Students studying Japanese at the main campus of the largest public university who have accommodated to face-to-face learning had to adapt to online learning sessions after the COVID-19 phenomenon emerged in early 2020. They had to learn independently and were expected to have digital technology skills in addition to having devices required for synchronous and asynchronous learning sessions. Would this change affect their motivation to learn Japanese? The researchers were motivated to undertake this study beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…Bagheri and Farhani (2022) found that students at an elementary level find learning English exciting because it offers knowledge beyond their mother tongue. Similarly, Abas et al (2023) noted that Japanese language learners exhibit integrative motivation, showing enthusiasm in class discussions, confident communication, and strong connections with peers. However, Abas et al (2023) also identified instrumental motivation among Japanese language learners, centered on achieving good grades and success.…”
Section: Literature Reviewmentioning
confidence: 94%
See 4 more Smart Citations
“…Bagheri and Farhani (2022) found that students at an elementary level find learning English exciting because it offers knowledge beyond their mother tongue. Similarly, Abas et al (2023) noted that Japanese language learners exhibit integrative motivation, showing enthusiasm in class discussions, confident communication, and strong connections with peers. However, Abas et al (2023) also identified instrumental motivation among Japanese language learners, centered on achieving good grades and success.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Similarly, Abas et al (2023) noted that Japanese language learners exhibit integrative motivation, showing enthusiasm in class discussions, confident communication, and strong connections with peers. However, Abas et al (2023) also identified instrumental motivation among Japanese language learners, centered on achieving good grades and success. Conversely, Kamaruddin et al (2020) encountered that English and Mandarin language learners in Malaysia are motivated by jobseeking opportunities, career advancement, and gaining knowledge.…”
Section: Literature Reviewmentioning
confidence: 94%
See 3 more Smart Citations